Typification of the name Salicornia deserticola (Amaranthaceae/Chenopodiaceae) - Piirainen, Mikko (Phytotaxa, 2015)
In connection with my account of Salicornioideae Ulbrich (1934: 449, 543) for the Euro+Med Plantbase (Piirainen 2009), I had to make a decision on the identity of Salicornia deserticola Chevalier (1934: 804), a species described from inland north Algeria near Touggourt. According to Chevalier (1934), it differs from the woody perennial “S. arabica L.” [a misapplied name for S. fruticosa (Linnaeus 1753: 3) Linnaeus (1762: 5)] mainly by its biennial life form and more slender stems, while it comes closer to the annual species of Salicornia Linnaeus (1753: 3).